The Effect Of Communication, Organizational Innovation and Motivation On Employee Job Satisfaction in The Agriculture and Food Service Of North Morowali Regency - Mukhtar Hamzah; Ayu Ratna Sari; Abdul Khalik; Haeruddin Haeruddin (Syntax Literate, 2022)
The purpose of this study was to determine and analyze (1) the influence of communication on employee job satisfaction at the North Morowali Regency Agriculture and Food Service, (2) the influence of organizational innovation on employee job satisfaction at the North Morowali Regency Agriculture and Food Service, (3) the influence of motivation on job satisfaction of employees at the North Morowali Regency Agriculture and Food Service. This study uses a quantitative approach using a population of 75 employees with sampling using a saturated sample using all members of the population as a sample. The method of analysis used is multiple linear regression method with hypothesis testing using the F test, T test and the coefficient of determination. The results showed that (1) communication has no significant effect on employee job satisfaction at the North Morowali Regency Agriculture and Food Service, (2) organizational innovation has no significant effect on employee job satisfaction at the North Morowali Regency Agriculture and Food Office, (3) motivation does not have a significant effect on employee job satisfaction at the North Morowali Regency Agriculture and Food Service.